Interdisciplinary approach for full mouth rehabilitation: A Case Report - ZAID AL-JEAIDI, (Asian Journal of Pharmaceutical and Clinical Research, 2016)
The demand for esthetic dentistry is ever increasing. A beautiful smile is considered as a symbol of health and vitality is now looked upon as a status symbol. Discoloration of the front tooth may severely affect the confidence of the patient. The use of dental implant presents a conservative and esthetic method of replacing missing teeth. Bleaching is recommended as a minimal invasive and cost effective approach to change the color of the teeth. This case reports the step by step procedure for full mouth rehabilitation of an esthetically demanding patient. Keywords: Bleaching, Composites, Esthetics, Implant, Root canal treatment.